ДО ПИТАННЯ ТЕРМІНОЛОГІЇ ПРОБЛЕМИ ГОЛОКОСТУ ТА ПІДХОДІВ ДО ОЦІНКИ ЦЬОГО ЯВИЩА (Zaporizhzhia Historical Review, 2021)
In the article is determined basic concepts and categories related to the problem of the Holocaust. It is proved to that the events of the Holocaust remain unique after the scales of total extermination of one ethnic group and in that be half does not have analogues in history of humanity.